Social Impacts of Education On Women Decision Making in Khyber Pakhtun Khwa, Pakistan (A Case Study of District Swat, Pakistan) - Majid khan; Rahamd Zaid; Muhammad Asghar Khan*; AsadUllah Khan; Maimona Adil (Social Science Review Archives, 2025)
Education has the main role in girls' socialization and their career growth. In this regard, this study investigates the complex influences of education on women's decision-making processes in Khyber Pakhtunkhwa, Pakistan, while they are thinking about their decision making in every aspect of life. It has long been understood that education is essential for achieving socioeconomic advancement and self-determination, especially for women who have historically faced obstacles in their personal and social life. The nature of this research study is qualitative while the primary data has been gathered with the help of an interview guide, (FGDs) focus group discussion. The data was collected from female students and house wife whose faced some obstacles in life, is the targeted population. The study conclusions show that women's early educations play a major influence on their decision to pursue further education and make them able to take decision in life. Furthermore, parents have a crucial role in helping daughters make decisions about continuing their education. Moreover, women are empowered to make decisions about their education because of family support and encouragement. On the other hand, societal perception has a significant impact in women's education. While urban culture values about girls' education since it strengthens their capacity for further study, rural society forbids females from pursuing higher education due to the conservative nature of its culture. Women also face difficulties in juggling their schooling with their family responsibilities, but they manage somehow as their early education gave them management skills. Furthermore, because to social and cultural constraints, the majority of women in Pashtun society are not permitted to pursue higher education outside. The ratio of male to female literacy is not equal. The study strongly suggests that the media should play its role in raising awareness and launching campaigns regarding education for all, high-quality education, hiring more female teachers, requiring teacher training, and community involvement in education promotion in order to close the achievement gap and further raise women's literacy levels.